Determination of Scale Inhibitor Effective Dose for Well A28 Using A Differential Scale Loop Method - Hardi, Maulana; Pratamora, Rene Indrawan; Wardani, Oktaviani Kusuma; Meisinca, Dzulhijah Nur (Scientific Contributions Oil and Gas, 2025)
Well A28 in the Rokan Field has been identified with scale deposition on the surface flowline. The Scaling Index (SI) calculated using the Stiff and Davis method was +3.89, showing a high potential for aggressive scale formation. These deposits originate from mineral precipitation in produced water. To address this issue, scale inhibitor injection was applied, and the optimum dosage was determined using the Differential Scale Loop (DSL) method. This method evaluates inhibitor performance based on differential pressure caused by scale formation under field conditions (temperature 127 °C, flow rate 5 mL/min, operating pressure 300 psi). Tests were conducted using inhibitor doses of 25 ppm, 35 ppm, and 50 ppm. The results showed that a dose of 35 ppm produced the highest inhibition efficiency, reaching 100.3%, while also exhibiting minimal pressure drop. This dosage proved more effective than the other concentrations evaluated. Identifying this optimum dose supports reductions in chemical consumption and maintenance frequency, offering practical and cost-efficient benefits for field operations.